Dynamic mechanical properties of epoxy/flax fibre composites. (September 2014) - Duc, Fabien; Bourban, Pierre-Etienne; Månson, Jan-Anders E
The mechanical and damping properties were measured for unidirectional, 0/90 and twill 2/2 flax fibre (FF) composites containing 40 vol% of fibres in an epoxy matrix. All composites were processed by resin transfer moulding. The influence of the impregnation quality, the fibre/matrix adhesion, the quality of the fibres, the twist angle of the FF yarns and the crimp in the FF fabrics on these properties were quantified. Twisted yarns in an unidirectional FF fabric impacted negatively on the stiffness while increasing the damping of about 57% through enhancement of the intra-yarn friction. In twill 2/2 fabrics, twisted yarns decreased Young's modulus owing to the induced crimp but increased the damping through enhanced inter-yarn friction. With improved fibre/matrix adhesion, a damping increase up to 109% was obtained through better activation of the intrinsic damping mechanisms of an elementary FF. The best compromise between damping and stiffness was obtained with FF having less dislocations.